IDENTIFICATION OF Staphylococcus sp. STRAINS ISOLATED FROM POSITIVE WIDAL BLOOD BASED ON 16S rRNA GENE SEQUENCES - Sri Darmawati (International Journal of Science and Engineering, 2015)
The purpose of this study is to identify 8 strains of Staphylococcus genus members isolated from positive Widal blood (4 strains of Staphylococcus saprophyticus, 1 strain of Staphylococcus warneri, 2 strains of Staphylococcus hominis, 1 strain of Staphylococcus xylosus and 1 strain of Staphylococcus capitis) based on 16S rRNA gene sequences. The methods used in this study are conducting PCR of 16S rRNA gene, cloning genes using T-Vector pMD20 which is transformed to E. coli DH5α, sequencing. The results show that four strains (BA 47.4, BA 19.2, KD 29.5 and TG 09.1) are identified as Stap. Saprophyticus strains of Stap. saprophyticus members of ATCC 15305T (99.01-100% similarity). The strain of TG 01.3 is identified as Stap. Warneri strain of TG 01.3 of Stap. Warneri members of ATCC 27836T (99.74-99.93% similarity), 2strains (KT 29.2 and KD 35.1) are identified as of Stap. hominis members of DSM 20328T (99.4-99.67% similarity). The strain of KT 30.5 is not identified